Cover: Journal of Basic Microbiology. 5/2016. (6th May 2016) - Unknown
Abstract : SEM micrograph (5000x) of Candida albicans biofilm grown in Lee's medium depleted with glucose and additioned with 5% xylitol. The field shows blastospores undergoing hyphal formation, and expresses the polyphenic trait of the fungus. Starvation conditions such as glucose depletion trigger hyphae formation which is considered a key virulence factor of the fungus. Studying the influence of carbohydrates and polyols on C. albicans growth is important in the perspective of a dietary control of infections by this opportunistic fungal pathogen. (Photo: Andrei C. Ionescu, Department of Biomedical, Surgical and Dental Sciences, IRCCS Galeazzi Institute, University of Milan, Milan, Italy).